Smoking Advertisements and Its Impact on Human Behavior - Afia Mushtaq *, Noman Arshed1, Muhammad Shahid Hassan (International Journal of Scientific Research and Management (IJSRM), 2016)
Advertisements facilitate households to respond to adjust behavior. This study has designed to examine the behavior of individuals about their future health behavior related choices in the light of pro- and anti- smoking advertisements respectively. Both advertisement follow the Health Belief Model which states that an advertisement must cover the cycle of exposure, recognition, receptivity and agreement respectively. This primary study which covers 222 respondents in order to judge the socioeconomic factors affecting the future decisions of the individuals about smoking using Multinomial Logit Model. This study concluded for pro-smoking advertisement, only T.V and movies are encouraging individuals to smoke. However; in anti-smoking advertisement, we have found T.V and movies & magazines and newspapers are also discouraging individuals to smoke. The study indicates that purchase of merchandise promotes individuals to smoke, whereas, the anti-smoking law is discouraging individuals to smoke.